Near surface mounted CFRP-based technique for the strengthening of concrete structures - Barros, Joaquim (2004)
To assess the effectiveness of the Near Surface Mounted (NSM) strengthening technique, an experimental program was carried out involving reinforced concrete (RC) columns and beams. In columns failing in bending the present work shows that the failure strain of the Carbon Fiber Reinforced Polymer (CFRP) laminates can be attained using the NSM technique. Beams failing in bending were also strengthened with CFRP laminates in order to double their load carrying capacity. This goal was attained and maximum strain levels of about 90% of the CFRP failure strain were recorded. Performance of externally bonded reinforcing (EBR) and NMS techniques was compared for strengthening RC beams failing in shear. NMS was much more effective, not only in terms of the increase of the load carrying capacity and deformability at beam failure, but also with respect to the time consuming nature of the corresponding strengthening procedures. To assess the bond behavior of CFRP to concrete, pulloutbending tests were carried out. The influences of bond length and concrete strength on the bond behavior were analyzed